Inside the mind of the shopper : the science of retailing - Sorensen, Herb, 1944-; Heckman, Mark; Sorensen, James; Bogomolova, Svetlana (Pearson Education, 2017)
World-Renowned Shopper Scientist Dr. Herb Sorensen Reveals: How Today's Shoppers Think, Behave, and Buy New Insights for Creating High-Profit Retail Experiences! In retail, there's only one number one. It's not Wal-Mart or Costco, or even Amazon: It's the shopper. To create high-profit retail experiences, you need to know exactly how your shopper thinks, feels, and acts at the point of purchase. Dr. Herb Sorensen illuminates today's consumer behavior in the context of radical technological and societal changes that are transforming retail. Building on these deep consumer insights, Sorensen introduces revolutionary new approaches to improving performance in self-service retail--whatever you sell, via bricks or clicks. You'll discover today's best ways to get the right items to the right customers when they want them... surpass the expectations of customers trained by online retail... own every consumer "moment of truth"! New coverage includes: Converging clicks and bricks into a super-high-efficiency retail engine Building the "webby store": visually managing every display like a web page Bringing product and shopper together via optimized navigation and search Measuring and promoting shopper efficiency Motivating long-cycle purchases: cars, tech, appliances, apparel, and more Speeding today's shoppers from "want" to "need"